PENGARUH CONSULTING FICILITIES, LIFESTYLE DAN CELEBERITY ENDORSER TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE MS GLOW (STUDI PADA MS GLOW LAMONGAN) - Roma Dhona Rahmawati; Didik Puji Wahyono; Sawabi Sawabi (JURNAL ILMIAH PENELITIAN MAHASISWA, 2023)
. This study aims to analyze and examine the influence of Consulting Ficilities, Lifestyle and Celeberity Endorsers on the Purchase Decision of Ms Glow's Skincare Products (Study on Ms Glow Lamongan). This study uses a quantitative descriptive approach. The population in this study is employees at PDAM Lamongan. The sample used in this study was Ms Glow Lamongan's consumers, amounting to 100 of the total population, namely 7,478 employee respondents. The data analysis method used in this research is using multiple linear regression analysis. Data analysis in this study was carried out using SPSS software. The results of data analysis show that organizational culture, work motivation and work discipline partially have a positive and significant effect on teacher performance. Then simultaneously Consulting Ficilities, Lifestyle and Celeberity Endorser on the Purchase Decision of Ms Glow's Skincare Products (Study on Ms Glow Lamongan)..